Preface - Abdullah, Zuraidah (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2017)
In this issue, Katha is focused on education system and development of educational levels in Thailand and Cambodia; multiculturalism in Indonesia; and a historical moderation policy in Malayonesia (the Malay world).